2020
DOI: 10.3390/ijms21249617
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Exerts Peripheral Inhibitory Effects on the Mouse Gastric Smooth Muscle through the AMPK Pathway

Abstract: Some adipokines, such as adiponectin (ADPN), other than being implicated in the central regulation of feeding behavior, may influence gastric motor responses, which are a source of peripheral signals that also influence food intake. The present study aims to elucidate the signaling pathways through which ADPN exerts its actions in the mouse gastric fundus. To this purpose, we used a multidisciplinary approach. The mechanical results showed that ADPN caused a decay of the strip basal tension, which was abolishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 52 publications
(49 reference statements)
3
20
0
Order By: Relevance
“…NO is considered as the major inhibitory neurotransmitter released from non-adrenergic, non-cholinergic (NANC) fibers supplying the smooth muscle and responsible for proximal stomach relaxation in both humans and rodents (Rand, 1992;Min et al, 2016;Idrizaj et al, 2021). In this view, we previously observed that a NO-dependent mechanism was implicated in the inhibitory actions of adiponectin on gastric smooth muscle activity (Idrizaj et al, 2018a;Idrizaj et al, 2019a;Idrizaj et al, 2020a). Interestingly, NO production has been shown to be also influenced by resistin in human vascular endothelial cells (Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…NO is considered as the major inhibitory neurotransmitter released from non-adrenergic, non-cholinergic (NANC) fibers supplying the smooth muscle and responsible for proximal stomach relaxation in both humans and rodents (Rand, 1992;Min et al, 2016;Idrizaj et al, 2021). In this view, we previously observed that a NO-dependent mechanism was implicated in the inhibitory actions of adiponectin on gastric smooth muscle activity (Idrizaj et al, 2018a;Idrizaj et al, 2019a;Idrizaj et al, 2020a). Interestingly, NO production has been shown to be also influenced by resistin in human vascular endothelial cells (Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Beside its effects on energy homeostasis, globular Adn has been shown to induce skeletal muscle differentiation of C2C12 murine myoblasts through a redox-dependent circuitry involving p38, Akt and AMPK signalling [ 13 ]. Moreover, Adn has been proven to cause alterations of the resting membrane potential and membrane electrophysiological properties as well as of K + and Ca 2+ currents, inhibiting smooth muscle contractility of the gastric fundus [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Idrizaj et al combined mechanical and electrophysiological methods, which further demonstrated that the effect of AdipoQ on K + or Ca 2+ current in SMCs was blocked in the presence of AMPK inhibitor (dorsomorphin). Meanwhile, western blotting analysis revealed that AdipoQ administration promoted the expression of phosphoAMPK (pAMPK) [95]. In addition, AdipoR1 was expressed by glial cells in the myenteric plexus, which was in keeping with the involvement of the AMPK pathway.…”
Section: Peripheral Effectmentioning
confidence: 88%